Designing and Building of 3D Adventure Game â€œTetuko: Childhood of Ghatotkachaâ€ Using Kinect - Basuki, Achmad; Nendra Putra, Jabbar (EMITTER International Journal of Engineering Technology, 2014)
Nowadays, the young people are not interested in the local culture as a â€œwayangâ€ puppet. This condition threatens the extinction of some of the local culture that should be a mainstay of the industry entering an era of creative industries. On the other hand, theyare more interested in playing computer games as changing of people's lifestyles. It becomes our basic idea to produce a game as a creative product. The genre of this game is fighting-adventure. This game depictures a story of fighting between the baby Tetuko and giant Kala Pracona. The game uses Kinect and 3D platform technology to attract more players to feel their adventures. With Kinect technology, the player can control the character with his gesture. Thus, this game will increase the awareness of young people about the culture of Wayang.KeywordsÂ : 3D game, kinect,adventure, local culture, creative industry.